Influence of Medical Education on Knowledge, Attitude and Practice of Self-Medication among Medical Students - Urvisha Gadara; Akanksha Prajapati; Kinnari Thacker; Vipul Chaudhari (Journal of Pharmaceutical Research, 2024)
Self-medication (SM) is the use of over-the-counter medication to treat self-diagnosed symptoms or disorders, or the continuation and reuse of prescribed medications for recurrent diseases without consulting a physician. Self-medication is very common practice now a days. Medical students are exposed to knowledge about diseases and drugs, which makes SM easier for them. Primary aim of this survey is to study the influence of medical education on knowledge, attitude, and practice of self-medication among medical students. Secondary aim is to evaluate the factors associated with self-medication. A cross sectional, questionnaire based analytical study was carried out in GCS medical college, Ahmedabad from November 2022 to May 2023. Data from 350 students were collected and analysed by using Microsoft Excel version 2019. Out of 350, 132 were from phase I, 80 were from phase II, 77 were from phase III and 61 were from phase IV. From phase I to phase IV, 75.7%, 85.8%, 82.3% and 87.4% students were having knowledge about SM respectively. 87.6% in phase I, 70% in phase II, 73.3% in phase III and 70.4% students in phase IV believed that the easy access to health care facility is the main reason for practicing the SM in medical students. The prevalence of SM was 23% in phase I, 71.25% in phase II, 76% in phase III and 83% in phase IV. The knowledge and practice of SM were more among phase I students compared to those in phase IV students.